Students’ Satisfaction with Blended Learning in a Public College in Chengdu, China - Bao, Yuanwei (Scholar: Human Sciences, 2025)
Purpose: The study comprehensively explores the impact of five independent variables: teaching presence, system quality, information quality, perceived usefulness, and self-efficacy. The dependent variable is students’ satisfaction. Research design, data, and methodology: The research utilized the Index of Item-Objective Congruence (IOC) to assess validity and employed Cronbach’s Alpha in a pilot test with 40 participants to establish reliability. Subsequently, 80 valid responses from students at Chengdu Vocational and Technical College of Industry were subjected to multiple linear regression analysis. This analysis aimed to ascertain the significant relationships among the variables. Following this, a cohort of 30 students participated in a 14-week strategic plan. The quantitative data obtained before and after the strategic plan implementation were compared using a paired-sample t-test, providing a comprehensive evaluation of the plan’s effectiveness. Results: In the multiple linear regression analysis, it was found that factors such as teaching presence, system quality, information quality, perceived usefulness, and self-efficacy significantly impacted students’ satisfaction. Additionally, the paired-sample t-test results indicated a notable difference in students’ satisfaction before and after the implementation of the strategic plan. Conclusions: This research is dedicated to identifying and implementing strategies that effectively meet students’ specific needs and expectations in this region, thereby contributing to an improved educational experience.